High hardness BaCb-(BxOy/BN) composites with 3D mesh-like fine grain-boundary structure by reactive spark plasma sintering - Borodianska, Hanna (2013)
Boron carbide B4C powders were subject to reactive spark plasma sintering (also known as field assisted sintering, pulsed current sintering or plasma assisted sintering) under nitrogen atmosphere. For an optimum hexagonal BN (h-BN) content estimated from X-ray diffraction measurements at ∼0.4 wt%, the as-prepared B a C b -(B x O y /BN) ceramic shows values of Berkovich and Vickers hardness of 56.7 ± 3.1 GPa and 39.3 ± 7.6 GPa, respectively. These values are higher than for the vacuum SPS processed B4C pristine sample and the h-BN -mechanically-added samples. XRD and electronic microscopy data suggest that in the samples produced by reactive SPS in N2 atmosphere, and containing an estimated amount of 0.3–1.5% h-BN, the crystallite size of the boron carbide grains is decreasing with the increasing amount of N2, while for the newly formed lamellar h-BN the crystallite size is almost constant (∼30–50 nm). BN is located at the grain boundaries between the boron carbide grains and it is wrapped and intercalated by a thin layer of boron oxide. B x O y /BN forms a fine and continuous 3D mesh-like structure that is a possible reason for good mechanical properties.